Waste solar panel generation in Viet Nam: waste estimation and management orientation - Phuong Ha, Tran; Vinh Hung, Ha; Duc Quang, Nguyen; Minh Trang, Vu; Duy Nam, Dao; Phuong Anh, Dinh Le; Thi Thu Huyen, Nguyen; Trung Hai, Huynh (Vietnam Journal of Science and Technology, 2024)
Solar energy has emerged as a prominent solution to address the rising energy needs of expanding populations and combat climate change. While the advancement and proliferation of solar photovoltaics have significantly contributed to the decarbonization of energy systems, the improper disposal of end-of-life solar panels could potentially result in significant environmental impacts. Moreover, lack of or inadequate information on the quantity of the obsolete solar panels and their related environmental impacts, as well as proper incentives, and regulatory policies on waste solar panel management are major hinderances for the safe disposal of waste solar panels their materials. In this case study, surveys at solar panel manufacturers, solar power plants and rooftop solar systems have been conducted. The collected information and data are then used to derive solar panel’s lifespan and estimate the amount of waste solar panel till 2050. It is estimated that the cumulative amount of waste solar panel generated in 2022 is about 148 thousand tonnes and is projected to increase to 1.7 million tonnes by 2050. Based on that, sound management solutions toward circular economy have been proposed to properly manage waste solar panel in Vietnam.